TUWO: MODEL SUSTAINABILITY DIGITAL MARKETING SEBAGAI JALAN PINTAS UMKM BERSAING DI ERA SOCIETY 5.0 - Febrianur Ibnu Fitroh Sukono Putra; Amron Amron; Diana Aqmala; Awanis Linati Haziroh (Sekolah Tinggi Ilmu Ekonomi AMA Salatiga, 2022)
Digital marketing is the answer to internationalization several obstacles of micro, small, and medium enterprises (MSMEs) in dealing with the society 5.0 era market dynamics. The virtual world has emerged as a promising platform for various marketing activities can significantly encourage MSMEs to improve business performance. The research aims to improve business performance by implementing a digital marketing sustainability model so it can be a solution for MSMEs to penetrate the international market in the society 5.0 era. The research method is an exploratory qualitative approach by collecting data based on in-depth interviews with related informants. The sampling technique is purposive sampling, in which the main criteria are MSMEs assisted by the Central Java Government. The research analysis flow is data collection, data reduction, data presentation, and concluding. The results show the